Dampening the signals transduced through hedgehog via microRNA miR-7 facilitates notch-induced tumourigenesis. - Vanina G Da Ros (Public Library of Science (PLoS), 2013)
Fine-tuned Notch and Hedgehog signalling pathways via attenuators and dampers have long been recognized as important mechanisms to ensure the proper size and differentiation of many organs and tissues. This notion is further supported by identification of mutations in these pathways in human cancer cells. However, although it is common that the Notch and Hedgehog pathways influence growth and patterning within the same organ through the establishment of organizing regions, the cross-talk between these two pathways and how the distinct organizing activities are integrated during growth is poorly understood. Here, in an unbiased genetic screen in the Drosophila melanogaster eye, we found that tumour-like growth was provoked by cooperation between the microRNA miR-7 and the Notch pathway. Surprisingly, the molecular basis of this cooperation between miR-7 and Notch converged on the silencing of Hedgehog signalling. In mechanistic terms, miR-7 silenced the interference hedgehog (ihog) Hedgehog receptor, while Notch repressed expression of the brother of ihog (boi) Hedgehog receptor. Tumourigenesis was induced co-operatively following Notch activation and reduced Hedgehog signalling, either via overexpression of the microRNA or through specific down-regulation of ihog, hedgehog, smoothened, or cubitus interruptus or via overexpression of the cubitus interruptus repressor form. Conversely, increasing Hedgehog signalling prevented eye overgrowth induced by the microRNA and Notch pathway. Further, we show that blocking Hh signal transduction in clones of cells mutant for smoothened also enhance the organizing activity and growth by Delta-Notch signalling in the wing primordium. Together, these findings uncover a hitherto unsuspected tumour suppressor role for the Hedgehog signalling and reveal an unanticipated cooperative antagonism between two pathways extensively used in growth control and cancer.